Placental transmogrification of the lung: two case reports and a literature review - Zhou, Hong-yuan; Li, Hong; Lu, Yu-jie; Wu, Heng-ping; Li, Yong-zhen (Frontiers in Medicine, 2025)
BackgroundPlacental transmogrification of the lung (PTL) is an uncommon benign lung lesion characterized by the presence of immature mesenchymal clear cells and frequent cystic changes.Case presentationWe report two cases. The first case was a 51-year-old woman who presented with chest pain and a history of pulmonary nodule detected during examination for over 1 month. The second case was a 58-year-old man with a smoking history who presented with progressive dyspnea and cough for over 1 month, and was found to have an asymptomatic pulmonary lesion. Computed tomography revealed localized cystic lesions in the first case and bullae in the second. Histological examination showed papillary structures resembling placental villi, lined by cuboidal epithelium without atypia, with hyalinized stromal cores containing capillaries and lymphoplasmacytic infiltration.ConclusionPTL exhibits placental-like architecture with CD10-positive stromal cells, suggesting it is a benign mesenchymal tumor rather than a form of emphysema. Pathological confirmation is essential, and surgical resection is the recommended treatment.